Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
I would go about solving this by elimination because the x variables are already the same so all you would have to do is change one equation to the opposite signs and add them, so it would look like:
7y + 5x = 19
+ -3y - 5x = -7
-------------------
4y=12
y=3
7y + 5x = 19
+ -3y - 5x = -7
-------------------
4y=12
y=3
7y + 5x = 19 ⇒ 21y + 15x = 57
3y + 5x = 7 ⇒ 21y + 21x = 49
-6x = 8
-6 -6
x = -1 1/3
7y + 5x = 19
7y + 5(-1 1/3) = 19
7y - 6 2/3 = 19
+6 2/3 +6 2/3
7y = 25 2/3
7 7
y = 3 2/3
(x, y) = (-1 1/3, 3 2/3)
3y + 5x = 7 ⇒ 21y + 21x = 49
-6x = 8
-6 -6
x = -1 1/3
7y + 5x = 19
7y + 5(-1 1/3) = 19
7y - 6 2/3 = 19
+6 2/3 +6 2/3
7y = 25 2/3
7 7
y = 3 2/3
(x, y) = (-1 1/3, 3 2/3)
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.